THE EFFECT OF MANAGERIAL OWNERSHIP, INSTITUTIONAL OWNERSHIP, AND OTHER FACTORS ON EARNINGS MANAGEMENT - VALESKA, MICHELLE; A. MULYANA, RICKY (E-Jurnal Manajemen Trisakti School of Management (TSM), 2023)
The purpose of this research is to obtain empirical evidence regarding the factors that influence earnings management in consumer non-cyclicals and consumer cyclicals companies listed in Indonesia Stock Exchange (IDX). The independent variables used in this research are managerial ownership, institutional ownership, firm size, leverage, profitability, sales growth, board size, and free cash flow. The population of this research are consumer non-cyclicals and consumer cyclicals companies listed in Indonesia Stock Exchange (IDX) with a research period of 2020-2022. The sample used in this research amounted to 66 companies with 198 data obtained from data collection techniques in the form of purposive sampling. The hypothesis testing method used in this research is multiple regression method. The result of this research found that profitability has a positive effect on earnings management. In contrast, institutional ownership and free cash flow have negative effects on earnings management. On the other hand, managerial ownership, firm size, leverage, sales growth, and board size have no effect on earnings management. A company who has higher profits will attract investors because the company will have a higher rate of return. This motivates management to perform earnings management. Companies with a higher percentage of institutional ownership and amount of free cash flow might substantially reduce their earnings management. Having more institutional ownership would reduce the discretionary accounting accrual activities and a higher amount of free cash flow shows that a company has enough money to meet its financial and operational needs.